From Cyberspace to Independence Square: Understanding the Impact of Social Media on Physical Protest Mobilization During Ukraine's Euromaidan Revolution. Issue 4 (2nd October 2019) - Brantly, Aaron Franklin
ABSTRACT: Cyberspace has dramatically affected social and political movements over the last 10 years. There is anecdotal evidence to suggest a strong role for information communications technologies (ICTs) in a changing landscape of organization and mobilization for large-scale social and political movements in countries around the world. This paper analyzes the 2013–2014 Euromaidan revolution in Ukraine using big data collected from open source content including blogs, Twitter, Facebook, YouTube, forums, and news sites and mixed methods and assess the ramifications and impact of social media on social mobilization. This work compares digital and physical engagement directionality and finds the impact of social media on physical protest turnout is significant and leads to increased numbers of protestors in the streets. The analysis also highlights means of developing and assessing social mobilization through the use of linguistically and regionally categorized social media.